Implementation of the Sabhara Unit Two-Wheel Patrol in Preventing theft Crimes - Ajeng Sekarningrat Ajeng (Tanggon Kosala, 2021)
Two-wheeled patrol carried out by the Ciamis Police Sabhara Unit is still not optimal in preventing the occurrence of criminal acts of fraud. This is evidenced by the increase in criminal acts of fraud every year. The purpose of this study is to describe and analyze the implementation of 2-wheeled patrol in Sabhara Unit in preventing fraud in the jurisdiction of the Ciamis Regional Police as well as the factors that influence the implementation of 2-wheeled patrol in Sabhara Unit in preventing criminal acts of curanmor in the jurisdiction of Polres Ciamis. Theories and concepts used to analyze this research are management theory, role theory, crime prevention theory, patrol concept, two-wheeled patrol concept and the concept of fraud. The research method uses a qualitative approach whose results are strengthened by the presence of findings, observations, document studies, and interviews with information sources. Techniques used for data analysis include data reduction, data presentation, and drawing conclusions. The results showed that the 2 (two) wheel patrol carried out by the Ciamis Police Sabhara Unit had already been carried out, but it was still not optimal because it had been shown to have increased in the last 3 years. This is caused by factors that hinder patrol implementation. Among them is the lack of communication between members of the 2 (two) patrol of the Sabhara Unit with the community which causes a lack of understanding from the community about maintaining harkamtibmas, not yet evenly distributed between the use of 2 (two) wheeled patrols with 4 (four) wheeled patrols, there are supporting and inhibiting factors. Based on the results of the study, the authors suggest that there is an increase in understanding of the importance of maintaining harkamtibmas socialized by members of the 2 (two) wheel patrol unit to the surrounding community, there is even distribution between the implementation of 2 (two) wheel patrol and 4 (four) wheel patrol which is carried out in accordance with the spirit that has been made, and increase the supporting factors for the implementation of 2-wheeled patrols and also minimize the inhibiting factors in the implementation of 2-wheeled patrol units in Ciamis Police Station.